2018
DOI: 10.3855/jidc.9916
|View full text |Cite
|
Sign up to set email alerts
|

Drug resistance and plasmid profile of uropathogenic Escherichia coli among urinary tract infection patients in Addis Abeba

Abstract: Introduction: Urinary tract infection is a major cause of morbidity and mortality worldwide. Uropathogenic Escherichia coli bacteria are the most common cause of urinary tract infections. Drug resistant Escherichia coli is results in high levels of treatment failure and can be a significant threat to survival of patients. Methodology: Escherichia coli bacteria were isolated using culture and conventional biochemical tests. Antimicrobial susceptibility testing and plasmid profile were performed using the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 22 publications
(46 reference statements)
2
5
0
Order By: Relevance
“…In this study high prevalence of drug resistance to ceftazidime (84%), ceftriaxone (80.5%), and cefotaxime (66%) was observed [52]. Resistance to ceftriaxone was observed in 80.5% of UPEC isolates, which is comparable to studies conducted in Nigeria 86% [13], India 81.8% [53] and China 84.8% [30], but higher than studies conducted in Nigeria 23.3% [54] and Mexico 10.2% [21].…”
Section: Discussionsupporting
confidence: 63%
“…In this study high prevalence of drug resistance to ceftazidime (84%), ceftriaxone (80.5%), and cefotaxime (66%) was observed [52]. Resistance to ceftriaxone was observed in 80.5% of UPEC isolates, which is comparable to studies conducted in Nigeria 86% [13], India 81.8% [53] and China 84.8% [30], but higher than studies conducted in Nigeria 23.3% [54] and Mexico 10.2% [21].…”
Section: Discussionsupporting
confidence: 63%
“…The activity of TMP-SMZ against UPEC in other regions of the world was significantly lower as the frequencies of TMP-SMZ resistant UPEC isolates ranged from 72.7% in Mexico to 82% in Pakistan (Ali et al 2016;Ramírez-Castillo et al 2018). High resistance to TMP-SMZ was also observed in Iran (54%), Ethiopia (68.5%), Mongolia (70.9%), and Jordan (73,1%) (Raeispour and Ranjbar 2016;Munkhdelger et al 2017;Regasa Dadi et al 2018;Shakhatreh et al 2018). These results indicate that in many countries TMP-SMZ should not be used in empiric UTI therapy due to the high frequency of UPEC resistant to this antimicrobial.…”
Section: Resistance To Trimethoprim-sulfamethoxazolementioning
confidence: 99%
“…(Abernethy et al 2017). Resistance to ciprofloxacin was significantly higher in developing countries (Ethiopia -85.5%, Nepal -64.6%, Pakistan -60.8%, Mongolia -58.1%, Jordan -55.5%) (Ali et al 2016, Khatri et al 2017Munkhdelger et al 2017;Regasa Dadi et al 2018;Shakhatreh et al 2018) than in developed countries (USA -5.1%, Germany -10.5%, Switzerland -17.4%, France -24.8%) (Lavigne et al 2016;Erb et al 2018;Hitzenbichler et al 2018;Yamaji et al 2018). The study conducted in Switzerland showed also that patient age over 65 years was associated with higher E. coli resistance to ciprofloxacin (Erb et al 2018).…”
mentioning
confidence: 98%
“…For instance, vancomycin and antistaphylococcal penicillin are used empirically to inhibit Staphylococcus aureus bacteremia; vancomycin is the rst choice for MRSA treatment [15][16][17]. Fosfomycin-trometamol and nitrofurantoin have been recommended as rst-line antibiotics for frequently uncomplicated cystitis; uoroquinolones are the oral rst-line treatment for uncomplicated pyelonephritis as E.coli is the leading uropathogen of uncomplicated urinary tract infections [18][19][20].…”
Section: Discussionmentioning
confidence: 99%